Enseñar Y Aprender: La Representación Mental De Docentes Y Estudiantes En Los Diferentes Niveles Educativos - Lis Rossi, Graciela (European Scientific Journal, ESJ, 2016)
The problem of how to change or improve attitudes toward teaching and learning, both in students and in experienced teachers, appears in all teacher training programs. The behaviors that make up this attitude generally sustained on certain common beliefs and social representations among teachers. This project represents an advance of an investigation performed in the National University of La Pampa (UNLPAM), setting as its object of analysis, the types of mental representation of teaching and learning maintained by teachers and students. One of its objectives consists in systematizing and analyzing the characteristics and singularities that this social construct provides, in relation to the different developmental stages and levels of formal education in which the subjects perform. For this reason, the "Educational Partner" test is used as a technique to apply to the sample. Thus, starting with the information achieved through the instruments applied and its statistical analysis, the results for teachers of are exposed Preschool and Initial educational levels. Significativ e contributions for the diagnosis, forecast and counseling in Educational and Evolutionary Psychology and Psychodiagnosis are expected, as well as those directed to the improvement of the quality of teaching and training.